THE IMPACT OF MIND MAPPING TECHNIQUE IN SOCIAL STUDIES COURSE ON STUDENTS' SUCCESS AND THE PERMANENCE OF KNOWLEDGE - Ayça KARTAL (Fırat University, 2019)
The aim of this study was to investigate the impact of mind mapping technique on students' success and permanence of knowledge in social studies course in the fourth grade of elementary school. The research, carried out as semi-experimental, was put into practice in the second term of 2010-2011 academic year for the fourth grade students of Köprüköy Primary School in Ardeşen, Rize. In the study, the class of 4-B (N=14) was determined as the control group while the class of 4-A (N=18) was determined as the experimental group. In the study, academic achievement test was used as data collection tools. Academic achievement test was developed to determine the exchange of academic achievements of the students by researchers. For the research, Mann Whitney U test was used in the Analysis of quantitative data (if the two groups) and in the comparison of the parameters between groups. Friedman test was used in order to determine whether there is a significant difference between pre test-final test of each group. Wilcoxon Signed Rank test was used as the post-hoc test. Results were evaluated at 95% confidence interval and p